A regulação do trabalho no programa de educação integral da Paraíba: a percepção dos docentes - Silva, Hedgard Rodrigues da (2022)
The creation of the Integral Citizen Schools was a landmark for the birth of the Integral Education Program of Paraíba (IEPPB), for the provision of full-time high school education, with a series of changes in the organization of the school and the teaching work. The IEPPB introduced a new curriculum with differentiated subjects, pedagogical practices for the student's life project, management tools for pedagogical and administrative monitoring, and implemented the Full-Time Teacher Dedication Regime (FTDR). This thesis sought to learn more about these changes, based on the perception of how high school teachers in FTDR interpret the process of regulating the teaching work in the IEPPB. To this end, it was established as the general objective of the research to understand how the changes in the process of the teaching work in the IEPPB impacted the professionalism of high school teachers in FTDR. The research methodology relied on quantitative and qualitative studies. Through documentary research and literature review, we sought to understand the most recent policy guidelines that inform the IEPPB. The field research was integrated with the research on ―The conditions of supply of public Basic Education in four states in the Northeast of Brazil,” developed by the Study Group on Educational Policy and Teaching Work of the Federal University of Minas Gerais. The data were collected through a questionnaire and focus group and analyzed using statistical treatment techniques and content analysis, delimited in the categories: workload, teacher evaluation, relationship with school management, autonomy, and remuneration and career. The results indicate that the teaching professionalism was impacted by workload, expansion and demands of pedagogical and administrative materials, instability of permanence in school, linking teaching autonomy to the results of students in external evaluations and dissatisfaction with the remuneration and career plan that do not reflect a policy of teacher appreciation. Thus, the IEPPB reinforces processes of teacher and school accountability that were already being employed in the state school system of Paraíba, being a reason for teachers' resistance through collective forms of organization and collaboration.